EVALUATION OF THE DRAFT REGIONAL REVENUE AND EXPENDITURE BUDGET OF KEDIRI COUNTY, EAST JAVA PROVINCE - Leksono, Totok Minto (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study aims to qualitatively evaluate the 2026 Kediri Regency Regional Revenue and Expenditure Budget (RAPBD) based on Permendagri Number 14 of 2025, focusing on 6 aspects: judicial compliance, schedule stages, details of Perda/Perkada, conformity of RKPD-KUA-PPAS, mandatory spending allocation, and spending posture. Qualitative research approach with case study research type. The results show high compliance through sub-activity adjustments, shifts in public school access spending, education allocation of 44.32% (exceeding the minimum of 20%), employee spending of 28.64% (below 30%), and village levy revenue sharing of 11.08% non-BLUD, although public service infrastructure of 26.28% has the potential for expansion. The findings confirm that SIPD-RI overcomes the KUA-PPAS time gap, recommends routine audits and automatic RKPD entries to optimize center-region synchronization and public services. The Regional Budget meets the principles of efficiency and transparency with an education allocation of 44.32% (above the minimum of 20%), control of employee spending of 28.64% (below 30%), and the revenue sharing of village levies of 11.08% non-BLUD. The significant adjustment strengthens fiscal stability, although public service infrastructure is still below the 40% ceiling, so there is potential for expansion. The responsiveness of the Regency Government to the poverty eradication and food self-sufficiency programs. The conclusion is that the evaluation of the 2026 Kediri Regency Regional Budget shows high compliance with the regulations of the Minister of Home Affairs through improving the juridical foundation, adjusting subactivities in SIPD-RI, and shifting strategic allocations for national priority programs such as People's Schools.